Textual Authority and Gender Justice: Interpretation of the Verse of Women's Testimony in Qs. Al-Baqarah (2): 282 from a Hermeneutical Perspective by Khaled M. Abou El-Fadlaled M. Abou El-Fadl - Eka Sulistiyawati; Ach. Faidi Rasyadi; Rahmat (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2025)
Many women are now experts in the fields of finance, business and muamalah, recognized globally, so there is no reason to prevent them from being witnesses. Witness eligibility should be based on competency, not gender. This verse needs to be understood contextually, by distinguishing between fixed religious teachings and those that can be adapted to the times. The main focus of this research is to explore the meaning of this verse, which is often debated regarding the role of women's testimony which is only half that of men's testimony. This research uses a qualitative research method with a type of library research, which relies on a study of literature and works relevant to this theme, including the hermeneutical thinking of Khaled M. Abou El-Fadl. The results of this research show that according to Abou El-Fadl, the interpretation of this verse must not only be seen from the historical context, but must also consider the principles of justice and equality in Islam. Thus, this research provides a new perspective in understanding gender justice in Islam, as well as how the authority of the text can be reviewed to create a fairer interpretation for women.